Effects on a Nearby Bridge of Dismantling Temporary Lining During Excavation of a Shallow-Buried Rectangular Tunnel - Sheng, Guilin; Wen, Sen; Wu, Fei; Liu, Shixing; Wang, Zhengzheng (Frontiers in Earth Science, 2021)
It is almost inevitable that when a tunnel is excavated in an urban area, it will pass under an existing bridge. During tunnel excavation, a temporary lining is installed and subsequently removed. However, dismantling temporary lining may affect the stability of a nearby bridge. A numerical model was created and tests were conducted on a large-scale physical model to investigate the effects of dismantling temporary lining on a nearby bridge structure. A novel method of modeling the restraining force at the top of a pier was introduced to make the model more accurate in representing the physical situation. Analysis of the results led to the following conclusions and suggestions. 1. The process of removing temporary lining can have a significant impact on surface settlement and structural deformation of the bridge. 2. The effect of removing the second half temporary lining is greater than that of removing the first half. The key range of the tunnel where this phenomenon is principally observed contains one section of tunnel ahead (i.e., in the direction of tunnel advance) of the bridge span and the two sections to the rear. 3. A 6 m–3 m–6 m mixed dismantling method is recommended for use in the key range, and a rigid cap-connection method is proposed to counteract the considerable effects of dismantling temporary lining.